2020
DOI: 10.3390/ijms21124260
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness in the Block by Honokiol, a Dimerized Allylphenol from Magnolia Officinalis, of Hyperpolarization-Activated Cation Current and Delayed-Rectifier K+ Current

Abstract: Background: Honokiol (HNK), a dimer of allylphenol obtained from the bark of Magnolia officinalis was demonstrated to exert an array of biological actions in different excitable cell types. However, whether or how this compound can lead to any perturbations on surface–membrane ionic currents remains largely unknown. Methods: We used the patch clamp method and found that addition of HNK effectively depressed the density of macroscopic hyperpolarization-activated cation currents (Ih) in pituitary GH3 cells in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 63 publications
(148 reference statements)
1
10
0
Order By: Relevance
“…Our further investigation strongly supported the hypothesis on the contribution of depressed I Ks on the prolonged APD in the aged cardiomyocytes. Our data are in line with previously published data: Indeed, studies have shown that the changes in a slow delayed rectifier channel can contribute to AP repolarization (Marx et al, 2002) and among them, a type of K + -channel, carrying slow outward K + -current, I KS , can contribute to the induction of prolonged APD, further leading to further cardiac arrhythmias through long-QT (Abbott, 2020;Chan et al, 2020;Huang et al, 2018;Wu & Sanguinetti, 2016). Similar findings in vivo PKG inhibitor applied aged rat cardiomyocytes were determined, as well.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our further investigation strongly supported the hypothesis on the contribution of depressed I Ks on the prolonged APD in the aged cardiomyocytes. Our data are in line with previously published data: Indeed, studies have shown that the changes in a slow delayed rectifier channel can contribute to AP repolarization (Marx et al, 2002) and among them, a type of K + -channel, carrying slow outward K + -current, I KS , can contribute to the induction of prolonged APD, further leading to further cardiac arrhythmias through long-QT (Abbott, 2020;Chan et al, 2020;Huang et al, 2018;Wu & Sanguinetti, 2016). Similar findings in vivo PKG inhibitor applied aged rat cardiomyocytes were determined, as well.…”
Section: Discussionsupporting
confidence: 93%
“…As the changes in a slow delayed rectifier channel can contribute to AP repolarization (Marx et al, 2002) and among them, a type of K + ‐channel (carries slow outward K + ‐current, I KS ; Abbott, 2020; Chan et al, 2020) can contribute to the induction of prolonged APD (leading to further cardiac arrhythmias through long‐QT; Huang et al, 2018; Wu & Sanguinetti, 2016), in this group of investigations, we first recorded the APs under KCNQ1/KCNE1‐channel current activator (1 µM for 30 min, ML‐277) in the aged cardiomyocytes. The representative original AP traces are given in Figure 3a.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IC 50 value required for its inhibition of I h or delayed-rectifier K + current was estimated to be 2.1 or 6.8 µM, respectively. HNK, or its structurally similar compounds, could exercise the pharmacological actions through its perturbations on ionic currents [ 4 ].…”
mentioning
confidence: 99%